Development of a T-Kick Technique Training Model at Pencak Silat Athlete Kijang Berantai - Basyir Basyir; Nevi Hardika; Ashadi Cahyadi (Universitas PGRI Pontianak, 2026)
This study aims to produce a training model for the T-kick technique at the Kijang Berantai Pencak Silat College that is valid, practical, and effective for trained martial artists. The research method used is Research and Development (R&D) by adopting the ADDIE model development procedures which include the stages of analysis, design, development, implementation, and evaluation. The research population was all adolescent martial artists at the Kijang Berantai College, while the research subject consisted of 30 martial artists taken using purposive sampling technique. Data collection instruments used feasibility assessment questionnaires for material experts and T-kick technique skill test instruments to measure achievements in martial artists' motor performance before and after the intervention. The data analysis technique applied combined qualitative descriptive analysis and quantitative analysis through the computerized Normalized Gain (N-Gain Score) enhancement test. Research findings from the pencak silat academic material expert validity team showed a feasibility percentage of 86% and from the pencak silat coach practitioner expert of 93%, both of which fell into the very feasible criteria. The results of the effectiveness test through descriptive statistical analysis showed an average N-Gain score of 0.59, which confirms that the effectiveness level of the training model is in the medium or effective category, with an increase in the distribution of scores from an initial average (pre-test) of 61 to 84 in the final evaluation (post-test). The conclusion of this study is that the integration of trajectory variance and movement angles designed through the ADDIE structure is proven to be highly valid and effective in improving the quality and stability of the T-kick technique in young martial artists.